Moving Beyond Movement: Diagnosing Functional Movement Disorder - Gilmour, Gabriela S.; Lidstone, Sarah C. (Seminars in Neurology, 2023)
Functional movement disorder (FMD) is a complex neuropsychiatric syndrome, encompassing abnormal movements and weakness, and is a common cause of potentially disabling neurological symptoms. It is vital to recognize that FMD is a syndrome, with nonmotor manifestations negatively affecting a patient's quality of life. This review highlights a diagnostic algorithm, where a history suggestive of FMD is combined with the presence of positive signs on examination and appropriate investigations to make the diagnosis. Positive signs indicate internal inconsistency such as variability and distractibility, and clinical findings that are incongruent with other known neurological disease. Importantly, the clinical assessment acts as the first opportunity to allow patients to understand FMD as the cause for their symptoms. Accurate and early diagnosis of FMD is necessary given that it is a treatable and potentially reversible cause of disability, with significant risk of iatrogenic harm associated with misdiagnosis.
Keywords: functional neurological disorder; functional movement disorder; diagnosis; pathophysiology; positive signs